Tingkat Pengungkapan, Transaksi COMPATIBILITY ANALYSIS OF THE LEVEL OF DISCLOSURE OF RELATED PARTY TRANSACTIONS WITH PSAK 7 (Study in a Manufacturing Company listed on the IDX): disclosure, related party transactions, Results of Analysis of Disclosure Level of Related Party Transactions in the Manufacturing Industry in 2022 - Akhmad Fikki Al Hidayah; Yulinartati, Yulinartati; Riyanto Setiawan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The purpose of this study aims to describe the level of disclosure of related party transactions in the manufacturing industry and compare between sectors as well as test and analyze its effect on firm value in manufacturing industries listed on the Indonesia Stock Exchange. Research Methods This research is a descriptive study using content analysis in related party reports in annual reports. To perform content analysis on a text, a code is given which is divided into several categories and then analyzed using conceptual analysis or relational analysis. Conceptual analysis functions to analyze and interpret the text by coding the text into manageable content categories. Meanwhile, relational analysis builds on conceptual analysis by examining the relationship between concepts in a text. The results of the study show that with regard to the Disclosure Practices of Related Party Transactions, manufacturing companies as well as other corporate entities listed on the Indonesia Stock Exchange (IDX) refer to the provisions of PSAK 7 of 2018. Related Party Disclosure Practices disclosed in the issuer's annual report can be grouped into 2 namely mandatory disclosure (mandatory disclosure) and voluntary disclosure (voluntary disclosure). The level of disclosure of related party transactions in manufacturing companies that are overall (oscore) gets a score of 64.4% and is categorized as a level of disclosure with moderate/medium compliance. The level of disclosure of related party transactions in manufacturing companies that are mandatory (mandatory) gets a score of 73.8% and is classified into a level of disclosure with a moderate level of compliance. As for voluntary disclosure, it gets a score of 58.2%. And can be classified into the level of disclosure with a low level of compliance.